The Education of Margot Sanchez - Rivera, Lilliam (New York Simon & Schuster BFYR, 2017)
Margot Sanchez is paying off her debts by working in her family's South Bronx grocery store, but she must make the right choices about her friends, her family, and Moises, the good looking but outspoken boy from the neighborhood.
Keywords: Hispanic Americans -- Juvenile fiction; Hispanic American families -- Juvenile fiction; Families -- Juvenile fiction; Conduct of life -- Juvenile fiction; Romance fiction; Hispanic Americans -- Fiction; Hispanic American families -- Fiction; Family life -- Fiction; Conduct of life -- Fiction; Love -- Fiction; JUVENILE FICTION / Social Issues / General (see also headings under Family); JUVENILE FICTION / Love & Romance; JUVENILE FICTION / Family / General (see also headings under Social Issues); Bronx (New York, N.Y.) -- Juvenile fiction; Bronx (New York, N.Y.) -- Fiction